渐开线样板测量装置测量不确定度的评定 - 柳强; 李睿思; 马勇; 王启明 (Jixie chuandong)
The main source of uncertainty of measurement while the involute master measuring apparatus measuring the involute cam which in the Y7125 grinder is analyzed,and on the basis of evaluating the uncertainty components,the expanded uncertainty is given.The result of evaluation shows that the measurement uncertainty of the involute master measuring apparatus is 0.45 μm.And the eccentric mounting error of basic circle wheel and mandrel is the main source of uncertainty of measurement.The measurement precision of the measuring apparatus could meet the requirements of measuring high precision of involute cam.